Flocking to fire: How climate and natural hazards shape human migration across the United States - Clark, Mahalia B.; Nkonya, Ephraim; Galford, Gillian L. (Frontiers in Human Dynamics, 2022)
As global climate change progresses, the United States (US) is expected to experience warmer temperatures as well as more frequent and severe extreme weather events, including heat waves, hurricanes, and wildfires. Each year, these events cost dozens of lives and do billions of dollars’ worth of damage, but there has been limited research on how they influence human decisions about migration. Are people moving towards or away from areas most at risk from these climate threats? Here, we examine recent (2010 to 2020) trends in human migration across the US in relation to features of the natural landscape and climate, as well as frequencies of various natural hazards. Controlling for socioeconomic and environmental factors, we found that people have moved away from areas most affected by heat waves and hurricanes, but towards areas most affected by wildfires. This relationship may suggest that, for many, the dangers of wildfires do not yet outweigh the perceived benefits of life in fire-prone areas. We also found that people have been moving towards metropolitan areas with relatively hot summers, a dangerous public health trend if mean and maximum temperatures continue to rise, as projected in most climate scenarios. These results have implications for policymakers and planners as they prepare strategies to mitigate climate change and natural hazards in areas attracting migrants.